Early development score as a prognostic factor in nonverbal/minimally verbal children with autism spectrum disorder: A matched case-control study in Cyprus - Margarita Kilili-Lesta; Konstantinos Giannakou; Louiza Voniati (Autism and Developmental Language Impairments)
Background and Aims Children with autism spectrum disorder (ASD) present with impairments in social interaction and stereotypic behaviors. About a third may exhibit delays in verbal expression beyond preschool age, potentially categorizing them as nonverbal/minimally verbal (NV/MV), a condition that can persist into adulthood and affect their quality of life. The risk and prognostic factors associated with this reduced verbal outcome remain uncertain. This study aims to identify such factors within children diagnosed with ASD in Cyprus. Methods In this case-control study, 56 children aged 3–12 years, with an ASD diagnosis, participated. Among them, cases were 22 children classified as ASD-NV/MV, and controls were 34 children classified as verbal (ASD-V), matched by age group and gender. Retrospective information on familial, perinatal, and developmental risk and prognostic factors were collected to calculate the familial risk score (FRS), perinatal risk score (PRS), and developmental risk score (DRS). Early development information was collected for the Early Development Score (EDS) and Early Gesture Score (EGS), to measure the children's skill level as toddlers across milestones. A low EDS and/or low EGS reflected general developmental delays and decreased frequency of early gestures and were considered in the DRS. A parent report questionnaire was utilized to determine the current overall linguistic level and status of participants, distinguishing cases from controls. Results Age group and gender-matched cases and controls were similar in socioeconomic status and demographic characteristics ( p  > .05). Among the various familial (e.g., sibling with ASD), perinatal (e.g., prematurity), and developmental (e.g., ASD regression) factors examined individually, as well as collectively as scores in a conditional logistic regression (CLR) model, only a high DRS ( p  = .03), due to low EDS ( p  = .04) was significantly associated with linguistic status. When considering all risk scores in a multivariate CLR model, children with a high DRS were more likely to belong to the cases than to the control group ( p  = .02). In a subsequent model with low EDS and low EGS, only the low EDS was significantly associated with the case group. Results showed that children with ASD and a low EDS, reflecting general delays in early development, were 4.5 times more likely to belong to the cases group than those with a high EDS ( p  = .02). Conclusions Early developmental delays in developmental milestones across various domains like gesture, motor, play, linguistic, cognition, and joint attention, in toddlerhood, were associated with later decreased verbal outcomes. Children in the sample with such early delays (low EDS), had a higher likelihood of persistent language delays (ASD-NV/MV) even at late school age. Future studies are needed to duplicate findings and explore possible contributing factors affecting linguistic outcome in ASD through prospective studies exploring within ASD differences. Implications These findings emphasized the importance of monitoring early development closely for children at risk for ASD, pre-diagnosis, to provide additional early support for those more likely to be ASD-NV/MV. Parents and specialists like pediatricians, educators, speech-language pathologists, among others, can track the EDS score of children at risk for ASD and refer to the appropriate specialists for early stimulation, intervention, and parent consultation promptly.